2022
DOI: 10.3389/fphar.2022.971164
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 preserves blood retinal barrier integrity in an in vitro model of diabetic retinopathy

Abstract: The impairment of the blood retinal barrier (BRB) represents one of the main features of diabetic retinopathy, a secondary microvascular complication of diabetes. Hyperglycemia is a triggering factor of vascular cells damage in diabetic retinopathy. The aim of this study was to assess the effects of vitamin D3 on BRB protection, and to investigate its regulatory role on inflammatory pathways. We challenged human retinal endothelial cells with high glucose (HG) levels. We found that vitamin D3 attenuates cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
0
11
0
1
Order By: Relevance
“…ZO-1 regulates the recruitment of mechanotransducers to the VE-cadherin complex [ 70 ], showing that TJs could modulate adherens junctions and endothelial function through an intricate molecular regulatory network. Hyperglycemia, oxidative stress, and inflammation are detrimental events that compromise ZO-1 expression in BRB [ 71 ]. Our data from ZO-1 immunodetection show a comparable pattern with that of VE-cadherin: HG conditions significantly reduced its expression, and co-incubation of HRECs with ASCs and, even more, with P-ASCs caused protein preservation.…”
Section: Discussionmentioning
confidence: 99%
“…ZO-1 regulates the recruitment of mechanotransducers to the VE-cadherin complex [ 70 ], showing that TJs could modulate adherens junctions and endothelial function through an intricate molecular regulatory network. Hyperglycemia, oxidative stress, and inflammation are detrimental events that compromise ZO-1 expression in BRB [ 71 ]. Our data from ZO-1 immunodetection show a comparable pattern with that of VE-cadherin: HG conditions significantly reduced its expression, and co-incubation of HRECs with ASCs and, even more, with P-ASCs caused protein preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D (calcitriol) has been demonstrated to have roles in animal and in vitro studies, such as lowering intracellular ROS and VEGF expression in retinal cells [ 36 ], decreasing cell damage from high glucose levels in animals [ 37 ], and being a potent inhibitor of retinal neovascularization in animal subjects [ 38 ].There are several forms of vitamin D, but the primary circulating form of vitamin D is serum 25-hydroxy-vitamin D3 (25(OH)D), and this is widely accepted as the indicator of vitamin D status [ 39 ]. Vitamin D insufficiency is defined as having a serum level of 25(OH)D below 30 ng/mL, whereas vitamin D deficiency (VDD) is defined as having a serum level of 25(OH)D below 20 ng/mL [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D has been studied more than other individual vitamins in general, not only in DR. There have been studies showing possible positive effects of vitamin D 3 on retinal cells in animals with DR [ 36 , 37 , 38 ], which seemed to hint at what could be expected in humans, and, therefore, encouraged many studies on vitamin D in DR. Regarding DR, while a number of studies found lower serum levels of vitamin D among patients with DR, compared to those without DR [ 32 , 43 , 44 , 45 , 46 , 47 , 48 , 50 ], other studies found no association between vitamin D serum levels and DR status [ 28 , 42 , 57 , 58 , 59 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, VEGF-induced permeability is mediated via Y685 phosphorylation and subsequent internalization of VE-cadherin [ 89 ]. Of note, previous in vitro studies showed that high glucose treatment greatly elevates the levels of VEGF mRNA and protein in ECs [ [90] , [91] , [92] ]. An increase in O-GlcNAcylation by OGA inhibitors also elevates VEGF expression, while, inversely, a decline in O-GlcNAcylation via OGT inhibition abolishes high glucose-prompted VEGF expression.…”
Section: Hbp and Retinal Ecsmentioning
confidence: 99%